Commercial Antithrombin Concentrate Contains Inactive L-forms of Antithrombin - Chang, Wun-Shaing W; Harper, Paul L (Thrombosis and Haemostasis, 1997)
The preparation of antithrombin concentrate for clinical use requires a viral inactivation step. In most commercial preparations this is achieved by heat pasteurisation. This process would be expected to alter the conformation of antithrombin from the active native species to an inactive latent (L-form) state (1, 2). To determine if this occurs during commercial preparation and to identify the proportion of the product in the inactive state, we examined the various antithrombin conformations within a therapeutic concentrate. The antithrombin concentrate was separated into five fractions by heparin-Sepharose chromatography. The fraction with the highest heparin affinity retained full activity, whereas the four fractions with reduced heparin affinity (~40% of the total antithrombin) had lost their inhibitory function. These inactive antithrombins were intact, monomeric, thermostable and resistant to unfolding in 8 M urea. Moreover, the protein patterns on isoelectric focusing and non-denaturing-PAGE showed that there were at least two different L-forms with isoelectric points separate from the native active species. Our findings demonstrate that approximately 40% of the antithrombin preparation examined exists as inactive l-forms. The clinical significance of administering this altered material is uncertain.